Caracterização de parâmetros meteoceanográficos em uma região costeira praial no Estuário do rio Pará - ANDRADE, Robinson da Cruz (2022)
The Amazon hydrographic basin is one of the most important watershed in the Brazilian northern region, having a drainage area of 6,112,000 km² and occupying 42% of the national territory, besides countless rivers and tributaries, covering 7 Brazilian states. The Cotijuba Island, is located on the Pará River Estuary (PRE), 109 km away from its mouth, under the influence of the Intertropical Convergence Zone (ITCZ). This Island has an area of 16.055km² and 20km of beach length, with the western portion bordering the mouth of the Guajará Bay. In the light of the foregoing, this work aim was to describe the mete-ocanographic aspects and physical-chemical parameters, according to climatic seasonality (rainfall and discharge conditions) and tidal variations. In this regard, were used pressure sensor such as CTD (Conductivity, Depth, and Temperature) and the meteo-oceanographic station as means of colleting wind, direction and precipitation, between the years 2017 and 2018. Salinity, temperature, and level values were also analyzed, as well as precipitation, wind speed and direction, besides the influence of the phenomenon El Niño South Oscillation (ENSO) on precipitation, in addition to analyzing these data through the kruskal wallis and Pearson correlation. The results obtained through the percentile showed that the physical-chemical data exhibited a high thermal amplitude caused by the seasonal oscillation in the analyzed periods, with both temperature and salinity having their maximum in the months of lowest rainfall recorded. The wind regime presented a tendency to north-northwest as the direction of greatest occurrence in September to November, and higher values of speed in the north-northeast in the months January to March; the precipitation presented maximums in February to March, with values at 300mm; the minimum was found in September to November, with values reaching 100mm. Pearson's correlation showed a high correlation between precipitation and wind speed in the periods from February to March and a high correlation between direction and precipitation in October. Keywords: estuary; compass rose; physical-chemical; Mete-oceanography; Pará river.